2013
DOI: 10.1177/0194599813512103
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Removal after Osseous Free Flap Reconstruction

Abstract: Objective Identifying risk factors for hardware removal in patients undergoing mandibular reconstruction with vascularized osseous free flaps remains a challenge. The purpose of this study is to identify potential risk factors, including osteocutaneous radial forearm versus fibular flap, for need for removal and to describe the fate of implanted hardware. Study Design Case series with chart review. Setting Academic tertiary care medical center. Subjects and Methods Two hundred thirteen patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 18 publications
9
57
0
Order By: Relevance
“…Donor site complications were similarly low, including a single radius fracture in each series (incidence 0.45% to 0.6%) (3,9). Notably, recipient site hardware exposure was 16% to 17%, a value that is higher than typically reported for the fibula flap (16,17), but consistently reported for the OC-RFFF (9,15). This complication occurred in one of the six patients (16.7%) in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Donor site complications were similarly low, including a single radius fracture in each series (incidence 0.45% to 0.6%) (3,9). Notably, recipient site hardware exposure was 16% to 17%, a value that is higher than typically reported for the fibula flap (16,17), but consistently reported for the OC-RFFF (9,15). This complication occurred in one of the six patients (16.7%) in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…In our series, the use of one osteotomy was a significant predictor of plate extrusion and osteotomies were more commonly utilized in FFF versus STFF. However, other studies have not found osteotomies to be predictors of plate extrusion (Day et al, ; Knott et al, ). In addition, anterior mandibular reconstructions were associated with a significantly increased rate of plate extrusion when compared to lateral mandibular reconstructions.…”
Section: Discussionmentioning
confidence: 95%
“…Deficiencies in soft tissue coverage may be an important factor in the development of plate extrusion. Several authors have noted that hardware exposure occurred at a higher rate in patients who underwent osseocutaneous radial forearm free flaps (OCRFFF) versus fibular free flaps (FFF), and concluded that this was likely due to the smaller amount of soft tissue incorporated in the OCRFFF (Day et al, ; Dean et al, ; Virgin et al, ). The subscapular system of free flaps makes available considerable soft tissue bulk with excellent mobility of the soft tissue relative to the bony component and generally provides abundant soft tissue coverage of the reconstruction plate (Gibber et al, ; Urken et al, ; Yoo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In patients who have a chronic infection and/or fistula, the social and economic impact of a draining wound, with repeated clinic visits and hospital admissions, can be significant. This technique forgoes a large skin flap elevation and dissection in a scarred operative bed without increasing risk to the facial nerve or causing cosmetic deformity.…”
Section: Discussionmentioning
confidence: 99%